Zwitterionic polyelectrolyte brush modified chitosan nanoparticles as functional biolubricant with good friction-reduction effect. (May 2023) - Yang, Lumin; Li, Renjie; Liao, Xiaozhu; Li, Tao; Kong, Yunsong; Zhao, Xiaoduo; Wang, Rui; Ma, Zhengfeng; Fan, Zengjie; Liang, Yong-min; Ma, Shuanhong; Zhou, Feng
Abstract: Osteoarthritis (OA) caused by the articular cartilage degeneration is closely related to the lubrication dysfunction of joint. At present, injecting biolubricants into the joint cavity is regarded as an effective strategy for the treatment of arthritis. Herein, a biocompatible chitosan (CS)-based nanoparticles (NPs) biolubricant (CS-PMPC@DS NPs) with dual function of lubrication and anti-inflammatory was fabricated. Zwitterionic polyelectrolyte brush poly(2-methacryloyloxyethyl phosphorylcholine, PMPC) was grafted onto the NPs via atom transfer radical polymerization (ATRP) strategy, while the anti-inflammatory drug (diclofenac sodium, DS) was encapsulated within them. Under the synergistic effect rolling lubrication and hydration lubrication mechanisms, the obtained biolubricant exhibited superior lubrication performance in either artificial joint materials or cartilage contacts, which presents great potential for OA treatment.